Mother-preterm infant interactions at 3 months of corrected age: influence of maternal depression, anxiety and neonatal birth weight - Neri, Erica; Agostini, Francesca; Salvatori, Paola; Biasini, Augusto; Monti, Fiorella (Frontiers in Psychology, 2015)
Maternal depression and anxiety represent risk factors for the quality of early mother-preterm infant interactions, especially in the case of preterm birth. Despite the presence of many studies on this topic, the comorbidity of depressive and anxious symptoms has not been sufficiently investigated, as well as their relationship with the severity of prematurity and the quality of early interactions. The Aim of this study was to evaluate the quality of early mother-infant interactions and the prevalence of maternal depression and anxiety comparing dyads of extremely low birth weight (ELBW) and very low birth weight (VLBW) preterm infants with full-term ones. Seventy seven preterm infants (32 ELBW; 45 VLBW) and 120 full term (FT) infants and their mothers were recruited. At 3 months of corrected age, 5 min of mother-infant interactions were recorded and later coded through the Global Ratings Scales. Mothers completed the Edinburgh Postnatal Depression Scale and Penn State Worry Questionnaire. Infant levels of development were assessed through the Griffiths Mental Development Scales. A relation emerged among the severity of prematurity, depression, anxiety, and the quality of interactions. When compared with the FT group, the ELBW interactions were characterized by high maternal intrusiveness and low remoteness, while the VLBW dyads showed high levels of maternal sensitivity and infant communication. Depression was related to maternal remoteness and negative affective state, anxiety to low sensitivity, while infant interactive behaviors were impaired only in case of comorbidity. ELBW’s mothers showed the highest prevalence of depressive and anxious symptoms; moreover, only in FT dyads, low maternal sensitivity, negative affective state and minor infant communication were associated to the presence of anxious symptoms. The results confirmed the impact of prematurity on mother–infant interactions and on maternal affective state. Early diagnosis can help to plan supportive interventions.